On the Initial Boundary Value Problems for Two Dimensional Systems of Zakharov Equations and of Complex-Schrodinger-real-Boussinesq Equations (Journal of Partial Differential Equations, 1992)
In this paper the author considers the initial boundary value problems for the system of Zakharov equtations (Za) and for the system of complex-Schr&#246dinger-real-Boussinesq equations (SBq) in a two-dimensional domain. He proves the global existence and uniqueness of smooth solutions of (SBq) and of (Za) by means of continuous extension method and a priori estilmates.
Keywords: (Za) equations (SBq) equations; compatibility conditions; a priori estimate